STUDI SIFAT MAGNET DAN SIFAT MEKANIS BAHAN MAGNET STRONTIUM HEXAFERRITE YANG DISINTESIS DARI STRONTIUM CARBONATE DAN HEMATITE - , M. IQBAL MUHARRAM R; , Ir. M.Waziz Wildan, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Magnet is a kind of material engineering that essential to be developed. Needs of this material are known increasing as long as the increase of the need and development in sectors of industry and electricity. In the discovery and the development of magnetic science, Strontium Hexaferrite (SrFe12O19) has been discovered as a kind of ferrite magnet that has a high coercivity. The making of this material has a low cost process. These characeristics are potentially explored and examined more to find the best method of producing SrFe12O19 that magnetically and mechanically has the optimum properties. The focus of this examination is finding the best temperature of calcination to synthesize SrFe12O19 and knowing the effects of sintering process to its magnet and mechanical properties. SrFe12O19 is synthesized by the reaction of mixing strontium carbonate (SrCO3) and hematite (Fe2O3). The â¤ 200 mesh powder of SrCO3 and Fe2O3 are selected then mixed by the ratio of 1 mol SrCO3 and 6 mol Fe2O3 in the turbula mixer for 5 hours. Afterwards the mixture calcined in 950 Â°C, 1000 Â°C, 1050 Â°C, 1100 Â°C, and 1150 Â°C, respectively holded for 5 hours. The results of those calcinations then characterized by XRD (X-Ray Diffractometer) so the best temperature of calcination to produce SrFe12O19 can be definitely defined. The powder of SrFe12O19 that calcined in the best temperature then uniaxially compacted by the 30 MPa pressure in order to make its 15 mm diameter cylindrical green body. The green body then sintered in 950 Â°C, 1000 Â°C, 1050 Â°C, 1100 Â°C, and 1150 Â°C with 1 hour of holding time to make it become sintered body. The density of sintered body then examined by the Archimedes method, and then its magnetic characteristics examined by VSM (Vibrating Sample Magnetometer) including the measurement of its magnetization (B) and magnetic field (H). The green body forming of a speciments also processed in a bar form for impact examination. The mechanical examinations of the speciments are including the examination of its hardness, pressure strength, and impact strength. The observation of speciments microstructure then obtained by the SEM (Scanning Electron Microscopy).